Dead but not gone: Female body, surveillance and serial-killing in Alfred Hitchcock's Frenzy. (1st November 2019) - Mondal, Subarna
AbstractAlfred Hitchcock in Psycho (1960) makes the corpse of an ordinary woman both an object of surveillance and a source of active watching. Mrs Bates and Marion in Psycho, Brenda and Babs in Frenzy (1972) may be seen as predecessors to the series of dead women figuratively staring back in films such as The Silence of the Lambs (Demme, 1991) and Perfume: The Story of a Murderer (Tykwer, 2006). The corpses do not merely offer themselves up as ciphers to be decoded. They reveal the lack in the perpetrators. Hitchcock's Frenzy relies on female bodies for clues to the murders. Hitchcock plays the vital role of bringing about a transition in the way in which women's bodies are to be treated in films, a transition from bodies shrouded by mist and darkness of the noirs to the exhibitionism of naked corpses in brightly lit settings. This article shows that abandonment of the usual tropes of visual impediments such as darkness and fog in Hitchcock's later films suggests a continually developing process of urban surveillance that aids in dehumanizing the victims. Further the post-murder masculinist investigative gaze forces a kind of mock-life on the victims through the relentless search of a killer's live signs on their dead flesh.